Art and Reality John Anderson on Literature and Aesthetics. - Anderson, John (Sydney University Press, 2017)
In Art and Reality, John Anderson explores how beauty is experienced and defined. He considers a wide range of topics, from Homer to Dostoevsky and Shakespeare, the Ern Malley hoax and censorship of Ulysses. With rigor and originality, Anderson proposes a philosophical approach to art that can lead us to thoughtful engagement with literature.